"Ahead of the Lawmen": Law and Morality in Disney Animated Films 1960–1998. (February 2017) - Nielsen, Laura Beth; Patel, Nehal A.; Rosner, Jacob
This article examines the relationship between law and morality in a selection of animated Disney movies released between 1960 and 1998. The authors analyze all of the fully-animated, G-rated movies that grossed 100 million or more (adjusted for inflation) which shaped the childhood of lawyers practicing today. We find that the predominant representation of the relationship between law and morality is that they are at odds. Law most often is portrayed as having no relationship to morality or, even worse, as an obstacle to justice. These findings have implications for theories of law and morality, justice, and ethics. These findings also raise provocative questions concerning the role of mass media and popular culture on children's moral development and understanding of the role of law.